The War on Terror in Comparative Perspective
X, 259 p.
Keywords: This book offers a thoughtful analysis of the international and domestic political impact of the global war on terrorism through the prism of US security relations in the wake of 9/11. Focused on regional and country-specific responses and consequences, the book considers the change and continuity in the international system.